Type and efficacy of online training for informal carers: a narrative review - D. Bressington; D. Bressington; D. Bressington; R. Gray; R. Gray; K. Barclay; K. Barclay; C. Overy; I. Blackberry; I. Blackberry; I. Blackberry (Frontiers in Public Health)
BackgroundThe need to provide training and support for unpaid informal carers of people with various health conditions is well established. This narrative literature review was conducted to explore recent evidence of informal carer eLearning education and training programs, and to guide the design of an online training program for Australian carers, including those living in rural and geographically remote settings.MethodDifferent combinations of relevant search terms were used across three databases: Google Scholar Advanced, MEDLINE with full text incorporating PUBMED, and CINAHL to search for literature published since 2014. Articles within peer-reviewed journals were chosen based on their topic relevance and strength of evidence.ResultsThe recent systematic reviews highlight that there is a lack of good quality research evidence for the range and efficacy of eLearning programs designed for carers of veterans and adults with disabilities, or mental health conditions, with most evidence related to carers of older people and people with dementia.ConclusionOnline educational programs for carers of older people and/or older people with dementia, and those with mental health conditions can improve carer well-being. Future programs should be co-designed with carers, evaluate care recipient outcomes, and address recruitment, retention, and information technology skills.